A functional scaffold to promote the migration and neuronal differentiation of neural stem/progenitor cells for spinal cord injury repair. (June 2020) - Liu, Weiyuan; Xu, Bai; Xue, Weiwei; Yang, Bin; Fan, Yongheng; Chen, Bing; Xiao, Zhifeng; Xue, Xiaoyu; Sun, Zheng; Shu, Muya; Zhang, Qi; Shi, Ya; et al.
Abstract: After spinal cord injury (SCI), endogenous neural/progenitor stem cells (NSPCs) were activated in neural tissue adjacent to the injured segment, but few cells migrated to the injury epicenter and differentiated into neurons. N-cadherin regulates mechanical adhesion between NSPCs, and also drives NSPCs migration and promotes NSPCs differentiation. In this study, linearly ordered collagen scaffold (LOCS) was modified with N-cadherin through a two-step cross-linking between thiol and amino group. The results indicated that N-cadherin modification improved the adhesion of NSPCs on collagen scaffold and increased the differentiation into neurons. When LOCS-Ncad was transplanted into complete transected rat spinal cords, more NSPCs migrated to the lesion center and more newborn neurons appeared within the injury site. Furthermore, rats transplanted with LOCS-Ncad showed significantly improved locomotor recovery compared with the rats without implants. Collectively, our results suggest that LOCS-Ncad may be a promising treatment option to facilitate SCI repair by recruiting endogenous NSPCs to the lesion center and promoting neuronal differentiation.